1988
DOI: 10.1016/0014-5793(88)80751-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential potency and trans‐activation of normal and mutant T24 human H‐ras1 gene promoters

Abstract: We have employed a short-term transfection assay system in which we monitored the transient expression of the chloramphenicol acetyltransferase (CAT) gene linked to the promoter region of the normal and mutant T24 H-rasl gene or the human s-globin gene in Chinese hamster lung (CHL) cells or cells derived from them which carry and express one or the other of the polyoma virus early genes. Our findings can be summarized as follows: (i) The mutant T24 H-rusl promoter region behaves as a stronger promoter than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Regulatory sequences have also been found in the first [21] and fourth [22] intron of the H-rasl gene. In the first case a six base pair deletion in the first intron of the T24 H-rasl gene increases transcriptional activity from the H-rasl promoter [21] whereas in the latter case a point mutation in the fourth intron is responsible for increased expression and transforming activity of the oncogene [22]. Moreover, it has been suggested that the regulation of H-rasl transcription may involve the Spl transcriptional factor since a number of Spl-binding sites have been found in the promoter region [23].…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory sequences have also been found in the first [21] and fourth [22] intron of the H-rasl gene. In the first case a six base pair deletion in the first intron of the T24 H-rasl gene increases transcriptional activity from the H-rasl promoter [21] whereas in the latter case a point mutation in the fourth intron is responsible for increased expression and transforming activity of the oncogene [22]. Moreover, it has been suggested that the regulation of H-rasl transcription may involve the Spl transcriptional factor since a number of Spl-binding sites have been found in the promoter region [23].…”
Section: Introductionmentioning
confidence: 99%